2003
DOI: 10.2527/2003.811217x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambient temperature on mammary gland metabolism in lactating sows1,2

Abstract: Two groups of three multiparous Large White x Landrace sows were used to investigate the direct effect of ambient temperature on mammary gland metabolism. Sows from the first group were exposed to temperatures of 28 degrees C between d 8 and 14 of lactation, and 20 degrees C between d 15 and 21; treatments were reversed in the second group. Four to six d after farrowing, an ultrasonic blood flow probe was implanted around the right external pudic artery and catheters were fitted in the right anterior mammary v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
79
1
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 36 publications
(57 reference statements)
14
79
1
14
Order By: Relevance
“…In accord with these results other studies showed the same pattern (RENAUDEAU et al, 2003b;WILLIAMS et al, 2013).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In accord with these results other studies showed the same pattern (RENAUDEAU et al, 2003b;WILLIAMS et al, 2013).…”
Section: Resultssupporting
confidence: 82%
“…ao desmame do que no TTCS (60,7±1,4kg (QUINIOU & NOBLET, 1999), increase in water intake (RENAUDEAU et al, 2003b), decrease in milk production (QUINIOU & NOBLET, 1999), failures in subsequent reproductive performance of sows (THAKER & BILKEI, 2005), increase piglet mortality by crushing and decrease piglet weight gain (MARTINS et al, 2008).…”
Section: O Objetivo Do Estudo Foi Avaliar a Influência De Diferentes mentioning
confidence: 99%
“…Resultados semelhantes foram observados por Lewis et al (1978), Noblet & Etienne (1989), Barb et al (1993), De Bragança et al (1998, Noblet & Etienne (1998), Renaudeau et al (2003) e Moreira (2003), que também constataram que a melhoria na condição ambiental de porcas lactantes resulta em aumento do ganho de peso de leitões. Recentemente, Wagenberg et al (2006), em estudo para avaliar o efeito do resfriamento do piso sobre o desempenho de porcas lactantes, também verificaram que os leitões provenientes de porcas mantidas sobre piso com resfriamento recebendo ração à vontade cresceram 22 g/dia a mais que os leitões das porcas mantidas em piso sem resfriamento.…”
Section: Resultsunclassified
“…De forma semelhante, Carvalho (1981), Schoenherr et al (1989), Lorschy et al (1991), De Bragança et al (1998, Quinou & Noblet (1999), Renaudeau et al (2003) e Moreira (2003) verificaram que porcas mantidas em ambiente com alta temperatura apresentaram maior número de movimentos respiratórios. O resfriamento do piso teve efeito (P<0,01), também, sobre a temperatura retal no período da manhã.…”
Section: Resultsunclassified
See 1 more Smart Citation